Analysis of EFL Students’ Difficulties in Learning English Phonology and Phonetics at English Department, Victory University of Sorong - Marissa Swanda Tupamahu; Sherly Gaspersz (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study analyzes the difficulties faced by EFL students in learning English phonology and phonetics at the English Department of Victory University of Sorong. The research involved 46 participants from the 5th and 7th semesters who had completed the English phonology and phonetics course. The findings reveal that students encounter significant challenges due to various factors, including interference from their first language (L1), inconsistencies in English spelling and pronunciation, and limited exposure to authentic speech and diverse accents. Additionally, cognitive constraints such as processing limitations and insufficient phonological working memory further hinder their ability to apply phonological theory in real-world communication. The lack of focused phonological training in the curriculum, combined with psychological barriers like pronunciation anxiety, also contributes to the students’ struggles. These findings highlight the need for enhanced phonological instruction, increased exposure to varied spoken English, and strategies to build student confidence, which are essential for overcoming the difficulties in mastering English phonology and phonetics.